Ba3Zr2Cu4S9: the first quaternary phase of the Ba–Zr–Cu–S system. (3rd August 2022) - Barman, Sayani; Jana, Subhendu; Panigrahi, Gopabandhu; Yadav, Sweta; Niranjan, Manish K.; Prakash, Jai
Abstract : Single crystals of a new semiconducting layered quaternary sulfide, Ba3 Zr2 Cu4 S9, are synthesized by the elemental reactions at high temperatures. This phase is the first member of the Ba–Zr–Cu–S system and represents an unprecedented structure type. Abstract : We report the synthesis of red-colored crystals of Ba3 Zr2 Cu4 S9 via a high-temperature reaction of elements at 1223 K. The title compound is the first quaternary phase of the Ba–Zr–Cu–S system. A single-crystal X-ray diffraction study has elucidated its crystal structure, which shows that it crystallizes in a new structure type in the centrosymmetric triclinic P 1̄ space group with cell dimensions of a = 6.9150(3) Å, b = 10.3863(5) Å, c = 12.2417(6) Å, α = 109.524(1)°, β = 105.132(2)°, and γ = 96.809(2)° with Z = 2. The asymmetric unit of the structure contains a total of eighteen crystallographic distinct atomic positions: 3 × Ba, 2 × Zr, 4 × Cu, and 9 × S. All these atoms are present at the general positions. The structure is best described as pseudo-two-dimensional with infinite layers of ∝2[Zr2 Cu4 S9 ] 6− and Ba 2+ cations occupy the space between two such layers. The Zr atoms are bonded with six S atoms to form ZrS6 octahedra. Each Cu(2) and Cu(4) atom sits at the center of a distorted tetrahedron of sulfur atoms. Interestingly, the Cu(1) and Cu(3) atoms are only three coordinated and form distorted CuS3 trigonal polyhedra. The ab initio DFT calculations are performed to explore the electronic structure and the optical properties. An experimental optical bandgap study established the semiconducting nature ( E g = 1.9(1) eV) of a polycrystalline Ba3 Zr2 Cu4 S9 sample in agreement with the theoretical DFT study. The computed cell constants and atomic positions are found to be in good agreement with the experiments. The computed bandgap is indirect with a ∼1.1 to 1.5 eV magnitude. The COHP values are obtained to assess the relative strength of chemical bonding between atoms. The relative charge transfer between bonding atoms is estimated from the analysis of the Bader charge.